2015
DOI: 10.1016/j.marpol.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

A GIS modelling framework to evaluate marine spatial planning scenarios: Co-location of offshore wind farms and aquaculture in the German EEZ

Abstract: a b s t r a c tThe concept of co-location of marine areas receives an increased significance in the light of sustainable development in the already heavily used offshore marine realm. Within this study, different spatial colocation scenarios for the coupling of offshore aquacultures and wind farms are evaluated in order to support efficient and sustainable marine spatial management strategies. A Geographic Information System (GIS) and multi-criteria evaluation (MCE) techniques were combined to index suitable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 40 publications
0
54
0
5
Order By: Relevance
“…They conclude that the economic and technological advancements are not considered well enough to overcome the biological boundaries for growth and production of fish in the Dutch North Sea. This is contradictive to Gimpel et al (2015) who concluded that integrated multi-trophic aquaculture (IMTA) production with haddock, seaweed and bivalves has potential for offshore production in the German North Sea. The reason for exclusion of haddock by Reijs et al (2008) was based on the low optimal temperatures for haddock (4-10°C; Fishbase) and the criteria that optimal temperature should be[12°C in order to deal with summer conditions.…”
Section: Feasibility Of Aquaculture In the Dutch North Seamentioning
confidence: 63%
See 2 more Smart Citations
“…They conclude that the economic and technological advancements are not considered well enough to overcome the biological boundaries for growth and production of fish in the Dutch North Sea. This is contradictive to Gimpel et al (2015) who concluded that integrated multi-trophic aquaculture (IMTA) production with haddock, seaweed and bivalves has potential for offshore production in the German North Sea. The reason for exclusion of haddock by Reijs et al (2008) was based on the low optimal temperatures for haddock (4-10°C; Fishbase) and the criteria that optimal temperature should be[12°C in order to deal with summer conditions.…”
Section: Feasibility Of Aquaculture In the Dutch North Seamentioning
confidence: 63%
“…Biological and technical cultivation seems feasible for a wider range of species such as the Pacific oyster, the flat oyster and scallops. However, the economic projections for these species are yet uncertain (Gimpel et al 2015;Pogoda et al 2011;Reijs et al 2008). The seaweed industry in the Netherlands is in its infancy.…”
Section: Feasibility Of Aquaculture In the Dutch North Seamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the scope for expansion of seaweed aquaculture beyond the currently suitable areas may be facilitated in the future by developments in offshore aquaculture, allowing cultivation (e.g., Sulaiman et al, 2015) and seaweed biorefining (Fernand et al, in press) in offshore farms (Lehahn et al, 2016). Current marine spatial models already propose solutions to competing demands for suitable space, such as the co-location of offshore wind farms and seaweed aquaculture (Gimpel et al, 2015).…”
Section: Global Seaweed Production and The Associated Co 2 Uptakementioning
confidence: 99%
“…The global growth of wind energy production will continue in the future because the use of this renewable source of energy is actively promoted by various institutions and associations (EWEA 2014). However, there are three main contentious issues associated with the development of wind energy: (1) discovering the trend of wind patterns (Tchinda et al 2000;Tchinda and Kaptouom 2003), (2) minimizing negative environmental impact by developing appropriate wind farm site selection criteria (Hwang et al 2011;Kaldellis et al 2013;Gimpel et al 2015;Latinopoulos and Kechagia 2015) and (3) identifying the environment impact of wind farms (Dai et al 2015).…”
Section: Introductionmentioning
confidence: 99%